Ecologically responsible entrepreneurship and its contribution to the green economy's sustainable development: Financial risk management prospects - Vladimir S. Osipov; Yuriy A. Krupnov; Galina N. Semenova; Maria V. Tkacheva (Risks, 2022)
This paper's goal is to develop a scientific methodology of financial risk management of ecologically responsible entrepreneurship for the sustainable development of the green economy. The originality of this paper is due to the fact that, for the first time, the financial risks of the green economy are considered through the prism of its sustainability. The paper's novelty is due to the modelling and quantitative measuring of the impact of the COVID-19 pandemic and the financial and economic crisis on the financial risks to the green economy's sustainability, in addition to the development of precise quantitative recommendations for financial risk management of the green economy. This enables an increase in its sustainability and reduces ecological disproportion in regions of the world (reducing the differences in the green economy's sustainability among regions of the world through the management of green investments). The paper's contribution to the literature consists of specifying the theory of financial risks to the green economy. According to the specified fundamental provisions of this theory, the essence of the process of green economy development is clarified (the "black box" is opened) as the increase in its contribution to sustainable development. As the indicator of achieving this development, an increase in the green economy's sustainability is offered. A new source of achieving the goal is proposed, consisting of a financial risk management of ecologically responsible entrepreneurship based on (private) green investments.
Keywords: 330; ecologically responsible entrepreneurship; financial risk management; green economy; sustainable development